2011
DOI: 10.1007/s10858-011-9577-2
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic relaxation enhancement to improve sensitivity of fast NMR methods: application to intrinsically disordered proteins

Abstract: We report enhanced sensitivity NMR measurements of intrinsically disordered proteins in the presence of paramagnetic relaxation enhancement (PRE) agents such as Ni(2+)-chelated DO2A. In proton-detected (1)H-(15)N SOFAST-HMQC and carbon-detected (H-flip)(13)CO-(15)N experiments, faster longitudinal relaxation enables the usage of even shorter interscan delays. This results in higher NMR signal intensities per units of experimental time, without adverse line broadening effects. At 40 mmol·L(-1) of the PRE agent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…In cases where NOE data were found limited, distances derived from PREs provided valuable supplemental restraints and permitted either characterization of the global folds for some proteins, [1,2] or delineate structural properties of disorder proteins. [3,4] Correspondence to: Angela M. Gronenborn, amg100@pitt.edu. Supporting information for this article is given via a link at the end of the document.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where NOE data were found limited, distances derived from PREs provided valuable supplemental restraints and permitted either characterization of the global folds for some proteins, [1,2] or delineate structural properties of disorder proteins. [3,4] Correspondence to: Angela M. Gronenborn, amg100@pitt.edu. Supporting information for this article is given via a link at the end of the document.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast NMR can be combined with SOFAST-HMQC 2D experiments into a single, relaxation optimized and spatially encoded tool [21]. During the preparation of this manuscript, another group reported that the addition of a paramagnetic nickel chelate improved the signal to noise ratio of SOFAST-HMQC experiments recorded for unfolded proteins [37]. Here, we show that 2D and 3D BEST sequences benefit from the presence of small concentrations of a gadolinium chelate for several different proteins, including both folded and unfolded examples.…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium may be preferred to nickel chelate due to its lower concentration requirements, 1 mM and 50 mM, respectively. Although nickel chelate has proven to enhance signal sensitivity for unfolded proteins using SOFAST-HMQC experiments [37], the pioneer work performed by Cai and collegues [23] seems to indicate that this effect is dependent of the water return to equilibrium. Indeed, their work suggests that for experiments with water flip back pulses, residues exposed to solvent experience signal reduction when fast pulsing is combined with Ni(DO2A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…153 The PRE may also be used for other than structural purposes. Theillet et al 154 proposed the use of PRE to improve sensitivity of fast NMR methods, illustrated by the case of intrinsically disordered proteins, in the presence of Ni(II) chelates. Saio and co-workers 155 described an NMR strategy for fragment-based ligand screeining using paramagnetic lanthanide probes.…”
Section: Paramagnetic Systems In Solutionmentioning
confidence: 99%